If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + -3z = 12 + -4y Solving -13 + -3z = 12 + -4y Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -3z = 12 + 13 + -4y Combine like terms: -13 + 13 = 0 0 + -3z = 12 + 13 + -4y -3z = 12 + 13 + -4y Combine like terms: 12 + 13 = 25 -3z = 25 + -4y Divide each side by '-3'. z = -8.333333333 + 1.333333333y Simplifying z = -8.333333333 + 1.333333333y
| y+14=3y+2 | | x-7*x*450=0 | | 0.16(36-24x)=0.66 | | 2x=1024 | | 2.5+8= | | z*3=2*(z+1) | | 7(9n+9)=315 | | 2x+4.5=21 | | 18x^2+216=0 | | ax+bk=t | | z*3=2*z+1 | | 7x^2-12x^2+5=0 | | 20-5m=45 | | -6a-(4b-12a+7c)= | | 2(2+3x)+2(2x-1)=3(x+6) | | 729=0 | | 7x+37=149 | | 5c+4=(-26) | | 9t+17=-1 | | 8t-9+4t=59-5t | | x+7=31 | | (x+14)+(3x-18)=180 | | (9x+2)+(2x)=90 | | 7(7-1*1)=42 | | 9(7t+6)=306 | | 15-10t+7+8t= | | -4(x+3)(x+3)+5=-8 | | 7x-7x-1=42 | | 68-5= | | x^2+19x+29=5x-4 | | x^2+4x=-7 | | x^2+2x-34=1 |